Розрахункове дослідження асинхронних генераторів з двома статорними обмотками в складі зварювальних комплексів з широтно-імпульсними регуляторами струму - Мазуренко, Л.І.; Джура, О.В.; Романенко, В.І.; Білик, О.А. (Технічна електродинаміка, 2012)
This paper represents the results of numerical research of steady-state performance of autonomous welding sources made with twowinding induction generators (IG) and PWM current regulators fed from uncontrolled rectifier connected to power winding. The calculations are made with electrically connected and disconnected IG stator windings and different values of input rectifier inductances. The core saturation in induction machines (IM) of different rated power is taking into account by revising a base experimental no-load characteristic. The recommendations concerning rated power determination of IM for generation mode depending on nominal welding current are presented.